Aggressive B‐cell lymphomas in the update of the 4th edition of the World Health Organization classification of haematopoietic and lymphatic tissues: refinements of the classification, new entities and genetic findings. (27th July 2017) - Ott, German
Summary: The update of the 4th edition of the World Health Organization Classification of Haematopoietic and Lymphatic Tissues portends important new findings and concepts in the diagnosis, classification and biology of lymphomas. This review summarizes the basic concepts and cornerstones of the classification of aggressive B‐cell lymphomas and details the major changes. Of importance, there is a new concept of High‐grade B‐cell lymphomas (HGBL), partly replacing the provisional entity of B‐cell lymphoma, unclassifiable, with features intermediate between diffuse large B‐cell lymphoma (DLBCL) and Burkitt lymphoma, the so‐called grey zone lymphomas. They either harbour MYC translocations together with a BCL2 and/or a BCL6 rearrangement (HGBL‐Double Hit) or HGBL, not otherwise specified (NOS), lacking a double or triple hit constellation. In addition, the requirement for providing the cell‐of‐origin classification in the diagnostic work‐up of DLBCLs, the role of MYC alterations in DLBCL subtypes, and newer findings in the specific variants/subtypes are highlighted.